A descriptive analysis of patients with stoma attending a tertiary hospital on the East Coast of Peninsular Malaysia - Abdul Wahab, Patimah; Mohamed, Nurhazelin; Ismail, Norsuzana; Hassan, Intan Idiana; Haryanto, Haryanto (IIUM Press, 2024)
Background: Stoma surgery is common among patients diagnosed with gastrointestinal disorders as part of treatment to save their lives and minimise the impact of the disease. However, there is a paucity of knowledge of their data, particularly in our study setting. The aim of this study is to descriptively analyse the characteristics of ostomy patients receiving treatment at a tertiary hospital on the east coast of Peninsular Malaysia. Methods: A retrospective observational study was conducted among ostomy patients attending a teaching hospital from 2016 to February 2021. Their electronic health records were reviewed and analysed. Data analysis was performed by using SPSS version 23.0. Descriptive statistical analysis was used to present the data. Results: A total of 48 patients were included. Their median age was 62.5 (interquartile range [IQR] = 14) and the median duration of living with a stoma was 10.5 months (IQR = 10). Most of them were men (70.8%), Malays (91.7%), completed secondary school or above (73.3%), and married (84.8%). Patients with ileostomy were 60.4%, colostomy 37.5% and urostomy (2.1%). About 95.7% underwent elective stoma surgery. The primary indication for stoma formation was rectal and colon cancer (71.7%) followed by intestinal obstruction (19.6%). Conclusion: In this study, stomas are predominantly observed among men, with ileostomy and colostomy being the most common types, primarily indicated for colorectal cancer. Further research is warranted to investigate the associated factors and impact of stoma formation on patients' daily life activities.